2008
DOI: 10.1080/10641960802279132
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Enalapril and Telmisartan on Clinical and Biochemical Indices of Sympathetic Activity in Hypertensive Patients

Abstract: Despite similar BP control, telmisartan attenuated autonomic balance more effectively than enalapril.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…This reflects a greater complexity of RRi series for patients from the CAD-group. Due to the inhibition of angiotensin II functions along with the consequent attenuation of vasoconstriction and sympathetic activity 38 ACE inhibitors lead to significant recovery of HRV indices, as observed through linear methods, which implies an improvement in the autonomic modulation of HR and a satisfactory prognosis 39 .…”
Section: Discussionmentioning
confidence: 99%
“…This reflects a greater complexity of RRi series for patients from the CAD-group. Due to the inhibition of angiotensin II functions along with the consequent attenuation of vasoconstriction and sympathetic activity 38 ACE inhibitors lead to significant recovery of HRV indices, as observed through linear methods, which implies an improvement in the autonomic modulation of HR and a satisfactory prognosis 39 .…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] There are several experimental evidences of antifibrillatory and antifibrotic effects of ACEI/ARBs probably by downregulating MAPK or ERK1/ERK2 expression and reducing collagenase activity. 53 A recent animal experiment 54 indicated that telmisartan inhibit sympathetic nervous system activity in obesity-induced hypertensive rats. In the research performed byLi et al, 50 it was found that dogs with ventricular tachypacing-induced congestive heart failure had a substrate for AF maintenance and the MAPK expression were increased, and treatment with enalapril significantly reduced these changes and attenuated the effects of congestive heart failure on atrial conduction, atrial fibrosis, and mean AF duration.…”
Section: Benefits and Possible Mechanisms Of Ras Blockade Therapy On mentioning
confidence: 99%
“…15 Telmisartan versus enalapril Thirteen trials involving 1682 patients compared telmisartan with enalapril. 5,[15][16][17][18][19][20][21][22][23][24][25][26] There was a greater reduction in both DBP and SBP with the use of telmisartan as compared with enalapril. Therapeutic response rates of DBP and SBP favored telmisartan (RR 1.15, 95% confidence interval (CI) 1.05-1.26; RR 1.18, 95% CI 1.02-1.38, respectively).…”
Section: Resultsmentioning
confidence: 99%